Flexing and the Ethics of Wealth in the Qur'an: A Maqasidi Interpretation of Qarun's Story in Q.S. Al-Qashas, Verse 76-82 - Hijjiyah , Syivaul Hikmatul; Maghfiratuzzahroh (Al-Karim: International Journal of Quranic and Islamic Studies, 2024)
This study aims to explore the phenomenon of flaunting wealth, commonly referred to as "flexing," through the lens of the Maqasidi interpretation framework developed by Abdul Mustaqim. The research seeks to elucidate the intended message behind the Qur’anic narrative of Qarun in Q.S. Al-Qashas: 76–82 and to uncover the Maqasidiyyah (objectives-based) values embedded within the text. Employing a qualitative library research approach with a descriptive-analytical method, the study uses primary data from the Qur’anic verses and secondary sources such as classical and contemporary tafsir literature, dictionaries, and academic articles. The findings reveal that the story of Qarun serves as a warning against excessive attachment to wealth, arrogance, and the neglect of social empathy. When contextualized within the modern phenomenon of flexing, the narrative highlights several key Maqasid al-Shariah, including Hifz al-Din (preservation of religion), Hifz al-Mal (preservation of wealth), Hifz al-Aql (preservation of intellect), and Hifz al-Nafs (preservation of life). In addition, the study identifies practical ethical values such as al-Insaniyah (humanity), al-Musawah (equality), and al-Mas’uliyyah (responsibility) that are relevant to contemporary societal behavior.Theoretically, this research demonstrates the potential of Maqasidi interpretation to serve as a dynamic framework for contextualizing Qur’anic teachings in light of evolving socio-cultural phenomena. Contribution: The study contributes to the growing body of literature on contemporary Qur'anic interpretation by bridging classical scriptural meanings with modern ethical challenges, particularly in relation to consumerism and identity expression in digital culture.